A Case of Congenital Cutis Laxa (Generalized Elastolysis). Issue 3 (3rd April 2005) - Champion, Paul; Ryan, Frank
Abstract : Cutis laxa (generalized elastolysis) is characterized by sagging folds of loose skin on the face and trunk. Although grouped with hyperelastic skin conditions such as Ehlers-Danlos syndrome, cutis laxa shows an almost total lack of skin elasticity. Because it is a generalized state, it may present as an abnormality in the connective tissue of more than one organ system. The authors report a patient who had end-stage renal failure related to heavy chain disease, a recognized association of cutis laxa. Although the patient's vascular abnormalities were significant, she died of respiratory failure at 41 years of age from cutis laxa-induced emphysema.